1984
DOI: 10.5006/1.3593905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Iron Oxide Dissolution—A Review of Recent Literature

Abstract: Recent literature concerning the dissolution of iron oxide and removal of iron oxide from metal surfaces is reviewed. Studies of electrochemical phenomena and reaction kinetics are discussed. Rate expressions based on this work are critically examined, and mechanisms for the dissolution of free iron oxide and iron oxide deposited on an iron surface are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…It has been shown that the mechanism of iron oxide dissolution in acidic conditions proceeds through a number of steps. 46 If the starting material is Fe 3 O 4 , it is first oxidized to γ -Fe 2 O 3 before undergoing further dissolution. Additionally, Fe 3 O 4 has a faster rate of dissolution than γ -Fe 2 O 3 under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the mechanism of iron oxide dissolution in acidic conditions proceeds through a number of steps. 46 If the starting material is Fe 3 O 4 , it is first oxidized to γ -Fe 2 O 3 before undergoing further dissolution. Additionally, Fe 3 O 4 has a faster rate of dissolution than γ -Fe 2 O 3 under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Fe 3 O 4 has a faster rate of dissolution than γ -Fe 2 O 3 under identical conditions. 46,47 Therefore, we suspect that the long term acid resistance of the hydrothermally treated mMS NPs is due to the oxidation that occurs during the hydrothermal treatment. Either the exterior shell or the entirety of the SPION is oxidized to γ -Fe 2 O 3 during the treatment, imparting mMS-hy samples with slower dissolution rates.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to iron powder, the presence of Fe(NH 4 ) 2 (SO 4 ) 2 also resulted in further decrease of inhibition performance of SCC2000. Iron may be dissolved in the carboxylate inhibitor solution at high tempera-tures (Frost et al 1974(Frost et al , 1976Frenier and Growcock 1984), and the dissolved iron may catalyze the degradation of the inhibitor molecules in the aqueous solution (Motekaitis et al 1980). Note that the exposure of steel surface as well as the iron concentration may be higher than that of a clean pipe, but it may represent a worst-case scenario for a highly corroded surface.…”
Section: Impact Of Stainless Steel and Iron On The Thermal Degradatiomentioning
confidence: 99%
“…Oxalic acid can be obtained cheaply as a by-product from other industrial processes and any remaining oxalate in the treated materials will decompose to carbon dioxide during the firing stage of ceramic making. Many researchers have studied the use of oxalic acid to dissolve iron oxide as a result (Vaglio et al, 1998;Segal and Sellers, 1984;Frenier and Growcock, 1984;Jepson, 1988;Panias et al, 1996;Blesa et al, 1987;Cornell and Schindler, 1987). Biological processes for iron removal have also been evaluated based on the use of several types of fungi, some being oxalic acid producing.…”
Section: Introductionmentioning
confidence: 98%